25 years of the Natura Sloveniae journal - Rok Kostanjšek; Nataša Mori; Matjaž Bedjanič; Maarten de Groot; Nina Šajna; Jernej Polajnar; Maja Zagmajster (Natura Sloveniae)
The article presents the history of the journal Natura Sloveniae over the 25 years, from 1999–2023, of its publication. The main aim of the journal is highlighted, as well as a brief analysis of the number of contributions and authors, the taxonomic groups covered in the articles, including an overview of the citation success of the articles published in the journal. In 25 years, 286 articles by 320 authors have been published in the journal. Over the years, the geographical scope of published articles has expanded from Slovenia to SE and Central Europe. A brief statistical analysis of the published articles shows the highest popularity of articles presenting species lists or new records for Slovenia. A considerable share of the contributions are focused on individual taxa, mostly insects, including butterflies and dragonflies. In its 25th year of publication, the journal, which is jointly published by the Biotechnical Faculty at University of Ljubljana and the National Institute of Biology, is switching to the digital submission and review system of the University of Ljubljana Press. In this year, a third, thematic issue is being published for the first time. After a quarter of a century of continuous publication, the journal occupies an important niche among Slovenian scientific biological journals and continues its mission to publish original scientific contributions in the field of biogeographical, biodiversity and ecological research in Central and Southeastern Europe and to encourage young authors to publish their field observations.